Adequacy of stress ulcer prophylaxis prescription in the intensive care unit: an observational study - Marilena Franchitti; Jitka Piubellini; Farshid Sadeghipour; Philippe Eckert; Pierre Voirol; Antoine G. Schneider (Swiss Medical Weekly, 2020)
PURPOSE